Adherence and persistence to oral anticoagulants in patients with atrial fibrillation: A Belgian nationwide cohort study - Grymonprez, Maxim; Capiau, Andreas; Steurbaut, Stephane; Mehuys, Els; Boussery, Koen; De Backer, Tine L.; Lahousse, Lies (Frontiers in Cardiovascular Medicine, 2022)
Background: Since non-vitamin K antagonist oral anticoagulants (NOACs) do not require coagulation monitoring, concerns of lower adherence and persistence to NOACs than vitamin K antagonists (VKAs) have been raised. Moreover, little is known on the frequency of permanent cessation and switching between anticoagulants in patients with atrial fibrillation (AF). Therefore, persistence, reinitiation, switching and adherence to oral anticoagulants (OACs) were investigated. Methods: AF patients with a first OAC prescription claim between 2013-2019 were identified in Belgian nationwide data. Persistence, reinitiation and switching were estimated using Kaplan-Meier analyses. Adherence was investigated using the proportion of days covered (PDC). Predictors for non-adherence and non-persistence were identified by multivariable logistic regression. Results: Among 277,782 AF patients, 69.6% NOAC and 37.2% VKA users were persistent after 1 year, whereas 44.3% and 18.9% after 5 years, respectively. After one year, 67.1% rivaroxaban, 68.1% dabigatran, 69.8% apixaban and 76.9% edoxaban users were persistent. Among subjects having discontinued NOAC or VKA treatment, 75.4% and 46.1% reinitiated any OAC within 5 years, respectively. VKAs were more frequently switched to NOACs than vice versa (17.6% versus 2.5% after 1 year). After one year, a high PDC (≥90%) was observed in 87.8% apixaban, 88.6% dabigatran, 91.3% rivaroxaban and 94.7% edoxaban users (90.2% NOAC users). Adherence and persistence were higher in older, female subjects, while lower in subjects with dementia or hyperpolypharmacy. Conclusion: Adherence and persistence to NOACs were high. However, 10% of subjects were non-adherent after one year and one-fourth did not reinitiate anticoagulation within 5 years after NOAC discontinuation.